Intelligence and Security Informatics for International Security Information Sharing and Data Mining - Chen, Hsinchun (Integrated Series in Information Systems,, 2006)
On September 11, 2001 the World became cognizant of the security challenges it faces on an international scale. With this awareness a commitment has come from the scientific, engineering, and health communities to help the world meet an array of security challenges. From these activities the science of "Intelligence and Security Informatics" is emerging, which will influence a new generation of policy makers, practitioners, researchers, and students. INTELLIGENCE AND SECURITY INFORMATICS FOR INTERNATIONAL SECURITY: Information Sharing and Data Mining presents a systematic national security research framework, and discusses IT technical components, and directions. The book reflects a decade of leading-edge research on intelligence and security informatics from the Artificial Intelligence Laboratory and the NSF COPLINK Center for Homeland Security Information Technology Research, as well as the application in real-world community situations by the center's director and the book's author, Dr. Hsinchun Chen.